Implementing Field Trip Using PJBL In Recount Text To Improve X MIPA 4 Students` Writing Ability At SMAN 2 Kediri - Harsiati, Srie Poedji Titis (Efektor, 2019)
The objective of the research is to determine : (1) Field Trip using Project-based Learning in recount text can improve X MIPA 4 students’ writing ability, (2) Field Trip using Project-based Learning in recount text can improve X MIPA 4 students` class atmosphere. This Classroom Action Research ( CAR ) is classified as qualitative descriptive research which uses three instruments; questionnaire, observations, and document analysis. Cycle 1 and Cycle 2 were conducted from March 9, 2018, until April 13, 2018, which involved 36 students of X MIPA 4 SMAN 2 Kediri in 2017/2018 Academic Year as the respondent. The researcher found that (1) in Cycle 1; the mean score is 80,42 which consists of 4 inaccuracy, 4,11 in developing ideas, 3,88 in generic structure, 4,03 in mechanics, (2) in Cycle 2 ; the mean score goes higher 87,36 which consists of 4,27 inaccuracy, 4,33 in developing ideas, 4,5 in generic structure, 4,27 in mechanics. Based on the data, it could be concluded that : (1) Field Trip using Project-based Learning in recount text can improve X MIA 4 students’ writing ability, (2) Field Trip using Project-based Learning in recount text can improve X MIA 4 students` class atmosphere.